Embolic stroke of undetermined source (ESUS) cohort of Brazilian patients in a university hospital - Modolo, Gabriel Pinheiro [UNESP] (2019)
Embolic stroke of undetermined source (ESUS) is an important group of cryptogenic strokes that are in evidence due recent ongoing trials. We reviewed medical records at discharge from the stroke unit of all patients who met ESUS criteria and attended our institution between February 2016 and July 2017. Among 550 stroke patients, 51 had ESUS. We found that hypertension (60%), diabetes mellitus (34%), and smoking (36%) were the most prevalent risk factors. The mean National Institutes of Health Stroke Scale (NIHSS) scores were 7 at admission and 4 at discharge, while median scores on the modified Rankin scale were 0 and 2 at admission and discharge, respectively. Our sample had similar ages, risk factors prevalence and NIHSS scores at admission and discharge when compared with European and North American cohorts. Although a small cohort, our study suggests that the ESUS population is similar in countries with different health financing.